2016
DOI: 10.1016/j.lfs.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of acotiamide, an orally active acetylcholinesterase inhibitor, into the myenteric plexus of rat and dog stomachs

Abstract: These findings suggest acotiamide distributes to the myenteric plexus of stomach, a putative site of acotiamide action, with adequate concentrations to inhibit AChE, in both of rat and dog stomachs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Additionally, its distribution into the stomach, the anticipated site of action for acotiamide, has been suggested to be facilitated using carrier-mediated processes from the blood. However, while several reports have described the distribution of acotiamide in the muscular layer of the stomach, little information on the mechanism of its transport is available. Therefore, we identified the uptake transporter responsible for distribution of acotiamide into the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, its distribution into the stomach, the anticipated site of action for acotiamide, has been suggested to be facilitated using carrier-mediated processes from the blood. However, while several reports have described the distribution of acotiamide in the muscular layer of the stomach, little information on the mechanism of its transport is available. Therefore, we identified the uptake transporter responsible for distribution of acotiamide into the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the pharmacokinetic properties and stomach distribution of acotiamide. Our previous studies have shown that acotiamide is highly concentrated in the stomach tissue of rats and dogs, suggesting that acotiamide acts on gastric nerves in the myenteric plexus in the gastric muscular layer. , The concentration of acotiamide in the stomach tissue could be associated with its pharmacological effect; however, there is no concrete molecular explanation for the mechanism of acotiamide accumulation in the stomach tissue after oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…Five days after brain operation, the rats were anesthetized with 10% chloral hydrate and gastric emptying and small intestinal transit time were evaluated. Acotiamide (N‐{2‐[Bis(1‐methylethyl)amino]ethyl}‐2‐[(2‐hydroxy‐4,5‐dimethoxybenzoyl)amino]thiazole‐4‐carboxamide monohydrochloride trihydrate (IUPAC)) was obtained from Zeria Pharmaceutical Co, Ltd. Acotiamide was dissolved in a 5 w/v% glucose solution, and rats were treated with acotiamide via subcutaneous injection at a dose of 30 mg/kg based on previous reports …”
Section: Methodsmentioning
confidence: 99%